Data from: Phylogeography of willow grouse (Lagopus lagopus) in the Arctic: taxonomic discordance as inferred from molecular data - Höglund, Jacob; Wang, Biao; Axelsson, Thomas; Quintela, María (Dryad, 2020)
Using independently segregating nuclear single nucleotide polymorphisms (SNPs) and mitochondrial control region sequences, we found an east–west division among sampled willow grouse Lagopus lagopus subspecies. This division cut across the range of the subspecies with the largest distribution (lagopus) and thus contradicted existing taxonomic classifications. Russian Lagopus lagopus lagopus tended to cluster with North American willow grouse partly classified as other subspecies. Scandinavian willow grouse (L. l. lagopus) clustered with red grouse from Britain and Ireland (Lagopus lagopus scoticus and Lagopus lagopus hibernicus) but substructuring confirmed the monophyly of the latter. In North America, we could not detect any major genetic divisions apart from two birds described as alexandrae from the Heceta Island (Alaska) when using mitochondrial sequences. Other samples from North America were intermingled regardless of whether they were described as muriei, alexandrae or lagopus. A specimen described as alexandrae was to some extent distinct when analysing the SNP data. The genetic analyses indicated some concordance between genetics and taxonomy but not complete congruence. This is particularly evident for mitochondrial DNA network analyses. We suggest that the taxonomy of this species would benefit by a careful re-examination of the available evidence for subspecies. It appears as if subspecies status is a poor proxy for assigning evolutionary significant units and management units in this species. WillowGrouse_SNP_data